Dampak Dokumentasi Elektronik terhadap Implementasi, Manfaat dan Hambatan pada Pelayanan Home Care - Agustina, Agustina; Has, Eka Mishbahatul Mar’ah; Indarwati, Retno (Journal of Telenursing (JOTING), 2024)
This study aims to determine the role of digitization in the documentation of nursing care for community nurses in home care services. Involving aspects of implementation, benefits and barriers in using electronic nursing documentation. The method used was using electronic databases such as Ebsco, Scopus, Proquest, and PubMed published between 2020-2023. Based on the initial search, there were 8 relevant articles out of 320 articles found. The results showed that the implementation of electronic nursing care documentation has a positive impact on patients, nurses and health services. However, several obstacles were found, namely the skills and knowledge of nurses on electronic documentation are still lacking, so training is needed. Internet network constraints are also very influential, especially in rural areas. In conclusion, there is a gap between the need for internet and internet distribution which is a challenge for the government in developing digitalization in the health sector and improving nurses' skills in electronic documentation. Keywords: Electronic Documentation, Barriers, Benefits